2003
DOI: 10.1034/j.1600-0463.2003.11101111.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance in stage I testicular cancer

Abstract: Treatment results on 695 stage I testicular cancer patients followed with surveillance are described. Seminoma (SGCT) was present in 394 patients and nonseminoma (NSGCT) in 301 patients. Relapses were detected in 155 patients (22%), in 69 patients with SGCT (17%) and 86 with NSGCT (29%). In patients with vascular invasion, relapse was detected in 54% of patients with NSGCT and 38% of patients with SGCT. Time to relapse was median 13 months (range 1 to 84 months) for SGCT and 5 months (range 1 to 171 months) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 57 publications
(64 reference statements)
2
67
0
5
Order By: Relevance
“…Daugaard et al (10) reported that 23 of 695 patients (3.3%) with Stage I testicular cancer including non-seminoma were LTFU before 5 years. In a longer-term observation, Choo et al (11) identified only three (3.4%) patients LTFU among 88 Stage I seminoma patients with a median follow-up of 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Daugaard et al (10) reported that 23 of 695 patients (3.3%) with Stage I testicular cancer including non-seminoma were LTFU before 5 years. In a longer-term observation, Choo et al (11) identified only three (3.4%) patients LTFU among 88 Stage I seminoma patients with a median follow-up of 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] The data in these series are now mature and relapse rates have consistently been reported to be about 15% in unselected patients with stage I disease. The predominant site of relapse in all studies was in the paraaortic lymph nodes; 41 of 49 (82%) of relapses in the Danish Testicular Cancer Study Group (DATECA) study and 57 of 64 (85%) in the Princess Margaret Hospital (PMH) series.…”
Section: Surveillancementioning
confidence: 99%
“…The survival outcomes are summarized in Table 5. 13,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The presence of microscopic vascular or lymphatic invasion in the primary tumour is the most important factor predicting relapse and the presence or absence of this factor has been used to divide patients: those with high-risk disease (a third of the cases) who have about a 50% risk of relapse, and those with low-risk disease who have about a 15% to 20% risk of relapse. 45 …”
Section: E25mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Three were randomized controlled trials, 9 were phase 2 trials, and 5 were from prospective institutional databases. For purposes of summary data generation, these studies included a total of 5561 patients ( Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%